2006
DOI: 10.3732/ajb.93.7.978
|View full text |Cite
|
Sign up to set email alerts
|

A stage‐based study of drought response in Cryptantha flava (Boraginaceae): gas exchange, water use efficiency, and whole plant performance

Abstract: Models of global climate change predict an increase in the frequency of major droughts, yet we know little about the consequences of drought for the demography of natural populations. This study examined a population of the semi-desert perennial Cryptantha flava (Boraginaceae) to determine how plants of different developmental stages respond to drought through changes in leaf gas exchange, leaf water potential, water use efficiency, growth, and reproduction. In two of the four years, drought was applied using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…This probably resulted in slow plant growth (smaller LAI), and also hastened senescence of older leaves. in agreement with the current results, studies conducted on Cryptantha flava revealed that larger plants were more sensitive to drought stress than smaller plants (Casper et al 2006). …”
Section: Discussionsupporting
confidence: 93%
“…This probably resulted in slow plant growth (smaller LAI), and also hastened senescence of older leaves. in agreement with the current results, studies conducted on Cryptantha flava revealed that larger plants were more sensitive to drought stress than smaller plants (Casper et al 2006). …”
Section: Discussionsupporting
confidence: 93%
“…Our data on gas exchange and twig growth suggest that small and large plants both responded to drought by limiting transpiration rates and reducing aboveground growth, as was also reported for Cryptantha flava (Casper et al, 2006). Reductions in canopy size in response to drought have been observed previously in L. tridentata growing near our field site (Allen et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…2a and b) were observed in conjunction with elevated transpiration. Increased growth in association with higher rates of water use has also been reported in the woody desert shrub Chrysothamnus nauseosus (Donovan and Ehleringer, 1991, though this was not the case in the drought adapted species Cryptantha flava (Casper et al, 2006) for which higher transpiration rates in small plants did not translate into increased growth.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent comparative study has shown a positive correlation between individual plant shrinkage and survival [52], but the importance of this phenomenon for population dynamics has often been overlooked. Plant shrinkage or dieback of shrub canopies is common during drought events [37,53,54], and negative size changes may occur over time even when severe drought is not apparent [31,39,55]. Sometimes the entire plant canopy dies, so dormant and dead plants are not immediately distinguishable [37].…”
Section: Precipitation Global Environmental Change and Desert Plant mentioning
confidence: 99%